Gambaran Akses Pelayanan Kesehatan Masyarakat Desa Sama Subur Kecamatan Motui Kabupaten Konawe Utara - Paridah; Hartati Bahar; Ruslan Majid; Afifa Yunizah; La Ode Muh. Alief Mahabbah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Access to healthcare services is a crucial determinant in improving community health, particularly in rural areas that face geographic and social challenges. This study aims to describe the accessibility and utilization of healthcare services among residents of Desa Sama Subur, Kecamatan Motui, Kabupaten Konawe Utara. A descriptive quantitative design was employed, with the population comprising all active household heads in the village. A total of 45 household heads were selected using total sampling. Data were collected through face-to-face interviews using structured questionnaires during the 2025 Field Learning Experience (Pengalaman Belajar Lapangan, PBL). Descriptive analysis was conducted and results were presented in frequency distributions and percentages.The findings indicate that the majority of respondents possess health insurance (88.9%); however, the utilization of healthcare facilities remains suboptimal, with only 48.9% having ever accessed services. Perceptions of healthcare accessibility varied, with 51.1% considering it easy and 46.7% reporting difficulty. Motorcycles were the most commonly used mode of transportation (77.8%), and community health centers (Puskesmas) were the most frequently utilized facilities (60.0%). Regarding service satisfaction, nursing staff behavior received the highest satisfaction rating (28.9%), while waiting time remained the main concern. In conclusion, healthcare access in rural communities is multidimensional, influenced not only by health insurance ownership but also by geographic factors, transportation availability, and service experience. Enhancing the utilization of healthcare services requires strengthening primary care and improving physical access to healthcare facilities.